FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAHIRAN DAN PENGGUNAAN KOMPUTER SERTA PENGARUHNYA TERHADAP KEMAMPUAN USER - Siti Astuti, Endang; Radjab, Enny (FIA UB, 2007)
This paper reports on a study at the Brawijaya University which investigated the factors which may affect end user sophistication in the use of computers. Quantitative data were gathered by survey from 126 computer users and structural equation modeling was used to test a conceptual model of user sophistication. The research findings emphasized the importance of computer self- efficacy, on-the-job opportunities to use computers, requisite training, and computer use; all were found to have effects on user sophistication. Task uncertainty was shown to negatively impact user sophistication. Important corroboratory evidence was also found for the role of computer self-efficacy in explaining IT-related behaviors. Overall, the research findings advance current understanding of how user sophistication is developed in, and influenced by, the working environment in this organization. The study concludes with a discussion of the implications for practitioners regarding the assessment and development of computing skills in the workplace. Keywords: End-user computing, user sophistication, self-efficacy, Brawijaya University